Return on investment in healthcare leadership development programs. Issue 1 (5th February 2018) - Jeyaraman, Maya M.; Qadar, Sheikh Muhammad Zeeshan; Wierzbowski, Aleksandra; Farshidfar, Farnaz; Lys, Justin; Dickson, Graham; Grimes, Kelly; Phillips, Leah A.; Mitchell, Jonathan I.; Van Aerde, John; Johnson, Dave; Krupka, Frank; et al.
Abstract : Purpose: Strong leadership has been shown to foster change, including loyalty, improved performance and decreased error rates, but there is a dearth of evidence on effectiveness of leadership development programs. To ensure a return on the huge investments made, evidence-based approaches are needed to assess the impact of leadership on health-care establishments. As a part of a pan-Canadian initiative to design an effective evaluative instrument, the purpose of this paper was to identify and summarize evidence on health-care outcomes/return on investment (ROI) indicators and metrics associated with leadership quality, leadership development programs and existing evaluative instruments. Design/methodology/approach: The authors performed a scoping review using the Arksey and O'Malley framework, searching eight databases from 2006 through June 2016. Findings: Of 11, 868 citations screened, the authors included 223 studies reporting on health-care outcomes/ROI indicators and metrics associated with leadership quality (73 studies), leadership development programs (138 studies) and existing evaluative instruments (12 studies). The extracted ROI indicators and metrics have been summarized in detail. Originality/value: This review provides a snapshot in time of the current evidence on ROI indicators and metrics associated with leadership. Summarized ROI indicators and metrics can be used to design an effective evaluative instrument to assess the impact of leadership on health-care organizations.